Temperature induced structural distortion and their effect on the physical properties of La0.6Sr0.4Mn0.8Co0.2O3 nanoparticles - M. A. Awad; Abdalrahman M. Rayan; I. A. Abdel-Latif; Mahrous R. Ahmed (Scientific Reports)
Abstract The current study presents an unprecedented detailed investigation of the structural, magnetic, electrical, molecular, morphological and compositional analysis of the La0.6Sr0.4Mn0.8Co0.2O3 (LSMCO) nanoparticles synthesized by the sol-gel method and calcinated at 650, 1000, and 1100 °C. Rietveld refinements and FTIR analysis, confirmed the formation of perovskite structure, where Rietveld output was used to trace the effect of calcination temperature on the overall structural properties. The Jahn-Teller distortion in LSMCO was inferred from the rhombohedral distortion, cooperative octahedral tilting/canting, electron distribution density, and shifts in Mn–O bond absorbance. The Halder-Wagner model and Scherrer equation were used for accurate crystallite size calculations. Thanks to structural analysis, the magnetic behavior and conduction mechanism in the LSMCO nanostructure were well explained. Magnetic analysis demonstrated superparamagnetic-like behavior at 1100 °C. Electrical measurements in the temperature range showed semiconducting behavior (298–473 K), where dual activation energies were identified. The activation energy at low temperatures (0.02–0.11 eV) was ascribed to bond length and bandwidth changes, whereas the activation energy at high temperatures (0.138–0.24 eV) was ascribed to polaron-mediated conduction and to Jahn-Teller distortion. These findings demonstrate the potential of using LSMCO nanoparticles in applications such as medical fields and in advanced magnetic storage systems.